BASMALAH AS A PROTECTION FOR BALA`: THE TRADITION OF WRITING BASMALAH EVERY 1 MUHARRAM AT ISLAMIC BOARDING SCHOOLS AL-MAHRUSIYAH LIRBOYO KEDIRI - Umayah, Rina Dewi; Zainal Abidin, Ahmad; Kusumawati, Ita Rahmania (The Department of the Qur'anic Studies, Faculty of Ushuluddin, Adab, and Da'wah, State Institute of Islamic Studies (IAIN) Langsa, 2022)
This paper discusses one of the unique phenomena of the living Quran, which is the tradition of writing Basmalah every 1 Muharram at the Al-Mahrusiyah Islamic Boarding School Lirboyo Kediri, which is done 113 times on a piece of paper, individually, without being known to others, and without speaking. This study explains how the santri (students) of Pondok Pesantren Al-Mahrusiyah practice the Basmalah tradition, the basis of the practice, and how the tradition is understood. Using a descriptive phenomenological method, this paper finds: first, this practice is carried out in a series of events, such as the reading of the end and the beginning of the year prayers followed by the giving of ijazah, then the santri (students) practice this tradition individually. Second, the basis used by the santri (students) refers to the KanzÅ«l an-najÄá¸¥ wa surÅ«r and KhazÄ«natu al-AsrÄr and á¸¤asiyah TafsÄ«r al-Baiá¸Äwi books. Third, based on the reading of Frazer's theory, it can be found that: 1) from the aspect of the Law of nature: the tradition of writing basmalah is prayer and hope or an effort to protect one's self to God, 2) from the principle aspect: santri write basmalah on a paper by writing which is attributed to certain phenomena, 3) from the practice side: using a series of prayers, and consists of several taboos that must be avoided, such as not being allowed to speak while writing basmalah. Overall, the above phenomenon shows the function of the Qur'anic verse as lidaf'i-l-al-bala` (repelling reinforcements), tahsÄ«n (fortress or protection), and jalbÄ«l manÄfi' (getting benefit).